Poverty, Riches and Social Citizenship - Melrose, Margaret. author. aut Link
XIV, 211 p.
Keywords: At a time when the gap between rich and poor has been increasing, Poverty, Riches and Social Citizenship provides an accessible introduction to current debates about inequality, exclusion and the nature of citizenship, while also presenting an innovative exploration of popular beliefs and values in Britain. The authors develop a series of conceptual models by which to understand the competing traditions which have informed ideas about citizenship, and the contradictory moral notions that currently inform popular expectations of the welfare state.